Calamansi (Citrus microcarpa Bunge) flavored lemon grass (Cymbopogon citrates) juice - Marabe, Marigold Pilaro
Five formulations of calamansi flavored lemen grass juice were prepared by varying the combination of lemon grass-water extract (LGWE) and pure calamansi extract (PCE).